328 Knowledge of sports related concussion in young sports athletes. (3rd March 2020) - Reid, Duncan; Hume, Patria; Whatman, Chris; Theadom, Alice; Walters, Simon; Fulcher, Mark; O'Reilly, Maureen; Mahon, Susan; Lough, Jules
Abstract : Background: One in five of all traumatic brain injuries (including concussion) are sustained within the sports and recreation context. Due to higher rates of participation in sport, young adults are at a particular risk. Over the last decade there have been a number of initiatives to increase concussion awareness within sports. Objective: This study aimed to explore current levels of knowledge towards concussion in New Zealand and to identify any gaps to inform educational initiatives. Design: Cross sectional anonymous survey. Setting: Recreational, community and national level sports. Patients (or Participants): Participants aged 16–21 were recruited via national sports organisations, local tournaments and via social media. Interventions (or assessment of risk factors): An anonymous, multi-choice questionnaire was completed either online or in hard copy between September 2018 and June 2019. Main outcome measurements: Percentage of correct responses to concussion knowledge items. Results: There were 1628 participants (Mean age 17.2, SD 1.6, 65.6% female) who completed the questionnaire. More than 80% of participants correctly recognised dizziness, headaches, blurred vision and confusion as signs of concussion. Awareness of other symptoms including amnesia, loss of consciousness nausea and insomnia were less well recognised (26- 74% correct). Only 35% of participants understood that players should not return to sport until symptoms have fully resolved, with a further 33.8% suggesting a player should wait between 3 and 4 weeks. There were no statistically significant differences in concussion knowledge between sports P<0=0.01. Conclusions: Whilst knowledge of some symptoms of concussion are high, there remain common important gaps in knowledge across sports. High diversity in response to return to play timeframes reflects inconsistency of messaging. The findings suggest the need for international concussion guidelines and education programmes that are cross sporting disciplines, with specific sports focusing on sport-specific issues such as helmet use and injury prevention strategies.